Development and characterization of sulfonated polysulfone membrane for proton exchange membrane fuel cell (PEMFC) - Naim, Rosmawati (2004)
Sulfonated polysulfone membranes with varying degree of sulfonation have been successfully synthesized by electrophilic substitution via sulfonation process in this study. Sulfonated dense membranes were fabricated using locally available pneumatically controlled casting machine. Characterizations of different degree of sulfonated polysulfone membranes were conducted through swelling effects, ion exchange capacity (IEC), Thermal Gravimetric Analysis (TGA), Differential Scanning Calorimeter (DSC), X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and proton conductivity measurement. It was observed that an increase in the degree of sulfonation increases the water uptake of the membranes and sulfonic acid group in the polymer membrane. From FTIR, it was clearly confirmed the occurrence of sulfonation in the polymer structure as the evidence of the SO3 stretching band was noticed at frequency of 1027 cm-1. It was found from TGA that the sulfonic acid group started to decompose at 250ÂºC and decomposition of the polymer main chain decreases by increasing the degree of sulfonation. The Tg value detected in this study was increased accordingly with the degree of sulfonation though some hindrance was found to decrease the Tg value during the experiments. Proton conductivity measurement of sulfonated polysulfone membrane was found to increase with operating temperature and degree of sulfonation. It was found that at higher temperature (80ÂºC), SPSU10 membrane exhibits proton conductivity value at par with that of Nafion 117 membrane. It was also observed from XRD analysis that dimethylformamide solvent was prone to form hydrogen bonding with sulfonic groups hence allows formation of a more regular structure which leads to an incipient crystalline character of the material structure. SEM micrographs showed clearly the altered microstructure of polysulfone polymer before and after the sulfonation process.